(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
Hydrogen is produced by several sources, particularly natural gas. Hydrogen production from methane steam reforming via a membrane reactor with CO2 capture is a unique method for simultaneously producing and purifying hydrogen and obtaining clean fuel. Methane steam reforming occupies 50% of hydrogen production in the world. CO2 capture can be divided into three fundamental types: post-, pre-, and oxy-combustion capture. However, carbon capture technologies include adsorption, absorption, membranes, cryogenic/low-temperature separation, or chemical looping combustion. MATLAB, COMSOL, Aspen Plus, and ANSYS These programs solve the governing equations for a sorbent-enhanced membrane reactor. These equations are continuity, mass, and heat transfer. We reviewed the technologies for CO2 capture related to hydrogen production, containing the types of hydrocarbon input, methods for production, catalyst types, CO2 capture materials, and operation conditions. Also, we summarized the technologies for CO2 capture studies in hydrogen production from natural gas steam reforming with membrane systems.